(untitled) (Estudios Gerenciales, 2013)
The paper analyzes the organizational learning process experienced in the design of a new packing servicefor the pharmaceutical sector, using the 4I model designed by Crossan, Lane and White (1999) and itsfurther developments. It was carried out an exploratory study using qualitative research methods. It wasfound evidence supporting the learning processes stated by the original model and its furtherdevelopments. The interviews and focus group results suggested that organizational learning is not alwaysa lineal process as stated by the model. Individual and group learning are parallel interacting and unfinishedprocesses. This study contributed to adding empirical evidence to the 4I model of organizational learningand its further developments, in a manufacturing firm.